Design and Implementation of a Caching Algorithm Applicable to Mobile Clients - Bžoch, Pavel; Matějka, Luboš; Pešička, Ladislav; Šafařík, Jiří (Informatica)
Design and Implementation of a Caching Algorithm Applicable to Mobile Clients